Seroinvestigation of Rubella virus of the oligozoospermia and azoospermia patients (Eurasian Medical Research Periodical, 2022)
The testis and epididymis are comparatively more relevant than accessory glands when it comes to inflammatory situations since they might become infected by microorganisms and become functionally compromised as a result